2022
DOI: 10.30968/rbfhss.2022.132.0791
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced liver injury causality assessment data from a crosssectional study in Brazil: a call for the use of updated RUCAM in hospital Pharmacy

Abstract: Objective: to identify the frequency of DILI inpatients from abnormal liver enzyme levels using the updated Roussel Uclaf Causality Assessment Method (RUCAM) causality assessment algorithm, as well as to provide a descriptive analysis of DILI cases. Methods: we conducted a crosssectional study in a medium complexity hospital in southern Brazil. Data regarding DILI was collected retrospectively from electronic medical records (EMR) in 2015. Inclusion criteria were all adult patients (≥ 18 years old) who present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The top drugs causing RUCAM-based DILI worldwide have been assessed as to whether they were metabolized through CYP isoforms [62]. Literature provided highquality data on clinical features of DILI [1][2][3][4][5][6][7][8][9][10][16][17][18][19][20][21][22][23][24][25][26][27][28]39,64]. However, although most of the clinical features are well established, a variety of mechanistic steps remain unresolved in this complex disease.…”
Section: Basics Of Molecular and Mechanistic Toxicology In Dilimentioning
confidence: 99%
See 3 more Smart Citations
“…The top drugs causing RUCAM-based DILI worldwide have been assessed as to whether they were metabolized through CYP isoforms [62]. Literature provided highquality data on clinical features of DILI [1][2][3][4][5][6][7][8][9][10][16][17][18][19][20][21][22][23][24][25][26][27][28]39,64]. However, although most of the clinical features are well established, a variety of mechanistic steps remain unresolved in this complex disease.…”
Section: Basics Of Molecular and Mechanistic Toxicology In Dilimentioning
confidence: 99%
“…Cessation of all non-essential drugs is mandatory as soon as the idiosyncratic DILI is suspected [13,28,29,90,91]. This alone has a positive effect on LTs as shown in many reports on DILI with verified diagnosis based on the RUCAM [1][2][3][4][5][6][7][8][9]. In most cases, a complete resolution of the liver injury is achieved, while in a few others, a protracted course of LTs is observed.…”
Section: Initial Therapy Of Dili By Drug Cessationmentioning
confidence: 99%
See 2 more Smart Citations
“…Advances and breakthroughs in the RUCAM field were also noted because for drugs which are implicated in iDILI, the updated RUCAM was increasingly used and mentioned for reasons of transparency in the title of virtually all publications [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Examples are case series with multiple drugs [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] as well as individual drugs in alphabetical order: androgenic anabolic steroid drugs (updated RUCAM score 6, probable causality grading) [ 34 ], atezolizumab (score 7, probable) [ 35 ], fluoroquinolones (scores 6–8, probable, and scores ≥9, highly probable) [ 36 ], methotrexate (scores 6–8/≥9, probable and highly probable) [ 37 ], nevirapine (scores 6–8, probable) [ 38 ], para-aminobenzoate (score 10, highly probable) [ 39 ], rosuvastatin (score 9, highly probable) [ 40 ], pazopanib (score 8, probable) [ 41 ], teriflunomide (score and causality grading not reported) [ 42 ], and tigecycline (scores as mean ± SD: 6.8 ± 0.7, probable, and 9.1 ± 0.3, highly probable) [ 43 ]. Analysis of the nine reports above showed that iDILI cases with a possible causality grading have also been included in a few of these publications, which should not be carried out because it clouds the robust clinical features provided by iDILI cases, for which probable and highly probable causalities were found.…”
Section: New Rucam-based Idili Casesmentioning
confidence: 99%